How to Improve Soil Anti-adhesion by Studying the Micro Relief of the Cuticle Surface of Digging Beetles: Exploring the Sulcophanaeus batesi Pronotum Using Translucent Replicas - Guillen, Noelia Belén; Setten, Lorena; Sánchez, María Victoria; Favret, Eduardo Alfredo (Oxford University Press, 2023)
For some years, we have been studying the microtopography of soil diggers beetles fromArgentina to find the anti-adhesion pattern to decrease a soil particle adhesion for agricultural machinery components. In 2018, we designed a macro topographic pattern for the upper surface of a steel shovel for tilling (agricultural tool) fromthe study of the microtopography (microrelief) of the cuticular surface of the pronotum of Diloboderus abderus (Coleoptera, Scarabaeidae), whose main feature is the presence of dimples randomly distributed.